Mechanical power output in rowing should not be determined from oar forces and oar motion alone - Hofmijster, M. J.; Lintmeijer, L. L.; Beek, P. J.; Knoek van Soest, A. J. (Journal of Sports Sciences, 2018)
Mechanical power output is a key performance-determining variable in many cyclic sports. In rowing, instantaneous power output is commonly determined as the dot product of handle force moment and oar angular velocity. The aim of this study was to show that this commonly used proxy is theoretically flawed and to provide an indication of the magnitude of the error. To obtain a consistent dataset, simulations were performed using a previously proposed forward dynamical model. Inputs were previously recorded rower kinematics and horizontal oar angle, at 20 and 32 strokes·min-1. From simulation outputs, true power output and power output according to the common proxy were calculated. The error when using the common proxy was quantified as the difference between the average power output according to the proxy and the true average power output (P¯residual), and as the ratio of this difference to the true average power output (ratiores./rower). At stroke rate 20, P¯residual was 27.4 W and ratiores./rower was 0.143; at stroke rate 32, P¯residual was 44.3 W and ratiores./rower was 0.142. Power output in rowing appears to be underestimated when calculated according to the common proxy. Simulations suggest this error to be at least 10% of the true power output.